Where the creek bends - Miller, Linda Lael (Canary Street Press, 2025)
"Madison Bettencourt has tried to assemble all the pieces of a perfect life, but nothing fits quite the way it should. She's moved back home to Montana to care for her grandmother, who is slipping further and further away. And she's called off her wedding, and worries her dreams of a family are fading with it. As Madison rattles around her family home, childhood memories come flooding back. Bliss Morgan transformed eight-year-old Madison with her loyalty, and for a while, the two girls were as close as can be. But Madison never understood why Bliss suddenly vanished, leaving only a friendship bracelet and a message etched into a matchbook"--
Keywords: Homecoming -- Fiction; Grandmothers -- Fiction; Caregivers -- Fiction; Best friends -- Fiction; Widowers -- Fiction; Man-woman relationships -- Fiction; Single fathers -- Fiction; Time travel -- Fiction; Montana -- Fiction; Domestic fiction; Romance fiction